Microbiome responses during virulence adaptation by a phloem‐feeding insect to resistant near‐isogenic rice lines - Horgan, Finbarr G.; Srinivasan, Thanga Suja; Crisol-Martínez, Eduardo; Almazan, Maria Liberty P.; Ramal, Angelee Fame; Oliva, Ricardo; Quibod, Ian L.; Bernal, Carmencita C. (Wiley, 2019)
The microbiomes of phloem‐feeding insects include functional bacteria and yeasts essential for herbivore survival and development. Changes in microbiome composition are implicated in virulence adaptation by herbivores to host plant species or host populations (including crop varieties). We examined patterns in adaptation by the green leafhopper, Nephotettix virescens, to near‐isogenic rice lines (NILs) with one or two resistance genes and the recurrent parent T65, without resistance genes. Only the line with two resistance genes was effective in reducing leafhopper fitness. After 20 generations on the resistant line, selected leafhoppers attained similar survival, weight gain, and egg laying to leafhoppers that were continually reared on the susceptible recurrent parent, indicating that they had adapted to the resistant host. By sequencing the 16s rRNA gene, we described the microbiome of leafhoppers from colonies associated with five collection sites, and continually reared or switched between NILs. The microbiomes included 69–119 OTUs of which 44 occurred in ≥90% of samples. Of these, 14 OTUs were assigned to the obligate symbiont Candidatus sulcia clade. After 20 generations of selection, collection site had a greater effect than host plant on microbiome composition. Six bacteria genera, including C. sulcia, were associated with leafhopper virulence. However, there was significant within‐treatment, site‐related variability in the prevalence of these taxa such that the mechanisms underlying their association with virulence remain to be determined. Our results imply that these taxa are associated with leafhopper nutrition. Ours is the first study to describe microbiome diversity and composition in rice leafhoppers. We discuss our results in light of the multiple functions of herbivore microbiomes during virulence adaptation in insect herbivores.